Next Steps for Education in Four Selected States in Brazil - World Bank (Washington, DC, 2013)
Despite an increased economic growth following the introduction of the Real Plan in 1994, the poverty rate in Northeast Brazil is not declining at par with that in other regions, aggravated by the fact that the Northeastern illiteracy rate, is twice as high as the national average. This report identifies exclusion from educational opportunities, suggesting ways to attain inclusion, based on an analysis of successful experiences, both in other parts of Brazil, and abroad. The analysis covers four states, selected on the basis of poverty incidence, and of educational failure and exclusion, as well as on the extent to which education authorities at the state level have expressed interest in educational reform. The study examines the determinants of educational exclusion, including that of rural, indigenous, and Quilombo (groups of slave descendants) children, stipulating there is a clear need for policymakers to adopt educational approaches that account for the many different perspectives of the Brazilian population, including the need to address geographical isolation, teacher qualification, the preponderance of over-aged students, and the lack of teaching support systems. Similarly, the study addresses the education of young adults, and their need for different education options, i.e., distance learning, accelerated classes, external certification, and modular courses. Moreover, school autonomy, and the financial aspects of education reform are examined, suggesting a focus on educational policies that increase educational access for vulnerable groups, reform of education management, and increased funding for education, by mobilizing public expenditure resources, and private sector financing.